Global, regional, and national burden of endometriosis among women of reproductive age, 1990–2021: Insights from the global burden of disease study 2021 - Jun Zhang; Mengduan Pang; Ling Li; Chuanjia Guo (PLoS ONE, 2025)
Background Endometriosis is a common gynecological disorder among women of reproductive age worldwide. This study aims to examine global patterns of endometriosis disease burden among reproductive-aged women and to evaluate its correlation with socioeconomic development indices. Methods This study conducted a comprehensive analysis of endometriosis disease burden using epidemiological parameters from the Global Burden of Disease (GBD) 2021 database, including incidence rates, prevalence rates, Disability-Adjusted Life Years (DALYs), and corresponding age-standardized rates. Through stratified analyses at global, regional, and national levels, we systematically evaluated the disease burden patterns among reproductive-aged women and performed correlation analysis with socioeconomic development indices. Results We found that the highest incidence of endometriosis among women of reproductive age globally occurs in the 20–24 age group, with an incidence rate of 399.49 per 100,000 in 1990 and 304.31 per 100,000 in 2021. The results show that the global disease burden of endometriosis is mainly influenced by population size, followed by epidemiological changes. Compared to countries with a medium Social Development Index (SDI), the disease burden of endometriosis in low and high SDI regions fluctuated significantly from 1990 to 2021. In most countries with SDI values between 0.2 and 0.6, the burden of endometriosis showed a gradual decline. Conclusion Endometriosis remains a significant public health issue for women of reproductive age globally. Although the global disease burden of endometriosis among women of reproductive age showed a slight decline from 1990 to 2021, the disease burden continues to fluctuate in certain regions and countries. In light of the differences in the disease burden of endometriosis across regions and countries, regionalized disease management strategies are expected to be developed in the future.